Water as a colorful ink: transparent, rewritable photonic coatings based on colloidal crystals embedded in chitosan hydrogel1. Issue 15 (21st April 2015) - Du, Xuemin; Li, Tengyue; Li, Lijun; Zhang, Zhicheng; Wu, Tianzhun
<x xml:space="preserve">Abstract</x> A rewritable and environmentally friendly paper using water as the ink is fabricated, and various colors can be achieved.